ENDOTHELIAL PROTECTIVE ACTIVITY OF 2,6-DIISOBORNYL-4-METHYLPHENOL IN A MODEL OF MYOCARDIAL ISCHEMIA/REPERFUSION IN RATS - PETR P. SHCHETININ; VERA I. SMOL’YAKOVA; TATYANA M. PLOTNIKOVA; ALEKSANDR V. KUCHIN; VLADIMIR V. UDUT (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Our research focuses on the endothelial protective effects of 2,6-diisobornyl-4-methylphenol. Its effect was revealed while studying rats experiencing myocardial ischemia/reperfusion. The research results demonstrated that there are significant disturbances in the vascular endothelium manifested by a decrease in the vasodilating activity and antiplatelet properties of 2,6-diisobornyl-4-methylphenol. Methods: We designed our own model of myocardial ischemia/reperfusion and applied it to 52 adult outbred Wistar males. We employed some methods of hemostasiological research such as thromboelastography to determine the antiplatelet activity of the vascular wall, G. Born nephelometric method to study platelet aggregation, phase contrast microscopy to count platelet counts in blood plasma, measurement of intra-arterial pressure to study the endothelial vasodilating function, and calculated the endothelial dysfunction coefficient in rats. Results: Preventive intragastric injection of 2,6-diisobornyl-4-methylphenol (100 mg/kg, 3 days before and 5 days after reproducing the myocardial ischemia/reperfusion model) increased the antiplatelet activity of the vascular endothelium in rats by 37% compared to the endothelium of the abdominal aorta segment of untreated animals. Moreover, 2,6-diisobornyl-4-methylphenol decreased the endothelial dysfunction coefficient by 43% in comparison with the value in the control group. Conclusion: 2,6-diisobornyl-4-methylphenol has an endothelial protective effect proved by its ability to increase antiplatelet properties of the endothelium and decrease the endothelial dysfunction coefficient. The revealed endothelial protective properties of 2,6-diisobornyl-4-methylphenol can be regarded as one of the potential mechanisms of cardioprotective activity of the drug.